Governing and Managing Public Service (A Case Study of Measuring Economic, Social and Environmental Implications of PDAM in the Malang City) - Andy Fefta Wijaya (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
Managing public water supply service delivery is a critical agenda. This research found that ineffective and inefficient governing systems of PDAM bring the economic, social and environmental implications. Particularly, the poor water users at the end of the water service delivery system get the more disadvantage consequences. Reforming governance and management of PDAM and implementing social and environmental friendly of performance measurement system is an alternative to increase the performance.Keywords: Public Management, Public Service, Governance, Accountability, Water Supply Service Delivery